Reciprocation with different motions: an in vitro comparative study - Vittorio Franco; Maya Feghali; Rosalie Chakra; Mohammed Hammo; Valentina Vincenzi; Kadriye Ozdayi; Hyeon-Cheol Kim; Massimo Galli; Gabriele Miccoli (Annali di Stomatologia)
A new clinical motion, designed to improve the safety and efficiency of NiTi instrumentation, has been proposed and positively evaluated in several studies: the “MIMERACI” technique. In the present study, the aforementioned technique was tested with a single-file reciprocating instrumentation system: EdgeOneR Utopia (Edge Endo, Albuquerque, New Mexico). The aim of the study was to determine whether the MIMERACI technique could reduce instrumentation stress (specifically torsional loads) by analyzing operative torque and comparing it to the traditional pecking motions recommended by manufacturers. Twenty instruments were randomly divided into two groups of 10 each. Each instrument in both groups was used to instrument one artificial 3D upper molar tooth. All teeth had identical anatomy, and three canals were instrumented to ensure proper visualization. Group 1 instrumented the canals using the MIMERACI technique, while Group 2 used a pecking motion (21) (1–2 mm amplitude) with a series of three pecking strokes. A video camera mounted on a tripod continuously filmed and recorded both the instrument’s progression inside the canal and the torque displayed by the motor. Torque values for both groups were recorded and transferred to an Excel sheet (measured every 1/10 second). Data were statistically analyzed using ANOVA and Tukey’s test at a 5% significance level. Group 1 (MIMERACI) demonstrated significantly lower average torque values (mean 0.25 N, SD 0.1) compared to Group 2 (pecking motion), which showed higher values (mean 0.45 N, SD 0.15). The maximum torque peak recorded was 1.4 N for the MIMERACI group and 2.2 N for the pecking motion group.